A experiência no Tai Chi: possibilidades para pensar o corpo sem órgãos e a preparação do ator - Vianna, Ana Carolina Strapação Guedes (2011)
Although research in the field of performing arts has substantially advanced over the last century, the actor, in general, still needs a repertoire of specific references to guide or support his practice. But how the actor must work the material foundation of his art that is his own body? Starting from a prerogative of a idiosyncrasy that is part of theater, this study intend, from the description and reflection about one physical experience with the Tai Chi, to weave relations between this experience and the possible developments of acting preparation. This research is also aimed to highlight the elements of connection between the principles that rules Tai Chi and the body without organs, idealized by Artaud, with the perspective of pointing possible contributions for actors work. The work presented here refers to a qualitative study that considers the body experience in practice of Tai Chi as a reference to dialogue and reflect about the acting preparation. The process of acting preparation presupposes a constant redoing of the body by certain practices. My experience with Tai Chi within this research allowed me verify that the work from established body techniques could be a way of technical preparation for the actor. As the body conscience expands, Tai Chi promotes a greater freedom of creation and expression, giving the actor the possibility of experience the body without organs, the artistic equivalent of the daily body, present, conscious, the organic foundation of emotions, in wich it is possible the materiality of ideas